2005
DOI: 10.1007/s10461-005-9032-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of Repeat HIV-Negative Testing: A Follow-Up Study

Abstract: Continued sexual risk behavior following repeatedly testing HIV-negative in the Polaris HIV Seroconversion Study (Ontario, Canada) led to this follow-up study which identifies the impact of repeat negative testing among 64 men and women. Repeat HIV-negative testing frequently results in confusion as to what constitutes risk and occasionally to thoughts of HIV immunity. Narrative accounts include beliefs that monogamy constitutes safety from HIV, that psychosocial factors other than repeatedly testing negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 6 publications
1
24
1
1
Order By: Relevance
“…These findings are consistent with previous studies in London (Leaity et al, 2000;Norton et al, 1997), Catalonia (Nascimento et al, 2004) and Ontario (Ryder et al, 2005), which found that repeat VCT acceptors were less likely to change their sexual behaviors following repeat VCT. In the Ontario study, most HIV-negative repeat testers described their sexual behavior and their perception of what constitutes risky sexual behavior as unchanged following repeat HIV-negative tests and some participants believed that the repeat negative test confirmed that their current sexual behavior, such as sex without a condom, was safe.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous studies in London (Leaity et al, 2000;Norton et al, 1997), Catalonia (Nascimento et al, 2004) and Ontario (Ryder et al, 2005), which found that repeat VCT acceptors were less likely to change their sexual behaviors following repeat VCT. In the Ontario study, most HIV-negative repeat testers described their sexual behavior and their perception of what constitutes risky sexual behavior as unchanged following repeat HIV-negative tests and some participants believed that the repeat negative test confirmed that their current sexual behavior, such as sex without a condom, was safe.…”
Section: Discussionsupporting
confidence: 92%
“…In the Ontario study, most HIV-negative repeat testers described their sexual behavior and their perception of what constitutes risky sexual behavior as unchanged following repeat HIV-negative tests and some participants believed that the repeat negative test confirmed that their current sexual behavior, such as sex without a condom, was safe. There were also beliefs among repeat HIV-negative testers that a repeat negative test following sexual risk behavior confirmed the belief that they were immune from HIV infection (Ryder et al, 2005). These findings suggest that HIV-negative persons who accept repeat VCT are more likely to engage in high-risk sexual practices, despite the potential benefits associated with repeat VCT education.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Some studies defined a "repeat tester" as someone who had tested more than once 22,23 , while others included in this category men who had had three or more tests in their lives 24,25,26,27,28,29 . Since the 2000s, the term "repeat testers" has been replaced by other notions of the frequency of repeat testing, more adequate for the new guidelines on frequent testing for MSM.…”
Section: Different Views Of Repeat Testingmentioning
confidence: 99%
“…However, some authors still interpreted the association between recent testing and unprotected anal sex as influenced by a feeling of invulnerability resulting from successive negative results 36 . A qualitative study on this theme revealed a broad mosaic of possible situations in the presence of repeated negative results 29 . The authors concluded that their data were worrisome, since for some individuals the negative results signaled immunity, while for others they reinforced the maintenance of practices that were not "100% safe"; meanwhile, in light of the risk reduction strategies, the interviewees' discourse gained another dimension.…”
Section: Recent Test As An Indicator Of Current Individual Carementioning
confidence: 99%